Development of an in vitro 3D co-culture system as an ameloblastoma disease model / Lee Soo Leng - Lee, Soo Leng (2018)
Ameloblastoma, the most clinically significant odontogenic epithelial tumour, is a locally-invasive and destructive lesion in the jawbones. Stromal cells as key contributors to the tumour microenvironment have a prominent role in tumour growth, progression and the spread of tumours. Therefore, the reciprocal parenchymal-stromal interactions in the milieu of the tumour microenvironment are inevitably capable of addressing the illunderstood nature of the infiltrativeness and destructive behaviour of ameloblastoma. Objective: An in vitro three-dimensional (3D) ameloblastoma tumour-osteoblast coculture model was established to elucidate the effect of heterotypic cell interactions on tumour growth and morphological characteristics of tumour cell. Materials and Methods: Stromal cell line, ST2 cells, pre-osteoblastic cell line, KUSA/A1 cells and osteoblastic cell line, MC3T3-E1 cells were separately co-seeded with the ameloblastoma tumour cell line, AM-1 in collagen gel incubated with mineralization medium. Results: AM-1/KUSA-A1 co-culture showed a heterogeneous cell population with two distinct morphologies: elongated spindle-shaped vimentin-positive cells with long anastomosing cytoplasmic processes interspersed and encircled cytokeratin-positive round cell which organized into nest-like aggregates. Both round cell with nest-like structures and elongated spindle-shaped cells in co-culture strongly expressed RANK, mildly for RANKL and OPG. 14-day-old KUSA/A1 monocultures shown evidence of intense extracellular matrix mineralization as confirmed by intense Alizarin Red S staining. In contrast, KUSA/A1 cells in the AM co-culture shown reduced Alizarin Red S staining revealed diminished calcification. Furthermore, 3D AM co-cultures showed a significant increase in AM-1 cell count compared to their monoculture counterparts, and formation of visible AM-1 epithelial nest-like structures resembling ameloblastoma cells in their native state. Conclusion: The in vitro 3D co-culture system as established in the present study provided some insights into the biological behaviour of enigmatic amelobastoma iv disease. Present in vitro findings suggest that, bidirectional ameloblastoma-osteoblastic interactions might play an important role in modulating tumour growth and local bone metabolism.